Adsorption of Copper on Transcarpathian Clinoptilolite - V.O. Vasylechko; G.V. Gryshchouk; L.O. Lebedynets; Yu.B. Kuz'ma; L.O. Vasylechko; V.P. Zakordonskiy (Adsorption Science & Technology)
The adsorption properties of Ukrainian Transcarpathian clinoptilolite in aqueous copper(H) solutions under dynamic conditions have been investigated. Under optimum conditions (p H of Cu 2 + solution = 7.1; adsorbent thermally modified at 120-170°C for 2.5 h; flow rate of Cu2+ solution through adsorbent = 3 ml/min), the adsorption capacity of the clinoptilolite towards copper amounted to 725 ng/g. The conditions for the desorption of copper(II) from clinoptilolite have been studied. Of the desorbents tested, the best were HNO 3 (1:1) and HNO 3 (1:2) solutions. Their effectiveness in extracting copper(II) ions under the desorption conditions employed amounted to 100%.